Microwave Assisted Extraction (MAE) of Castor Oil From Castor Bean - Nurfarahin, Harun (2013)
The purpose of this research is to extract the castor oil by using the microwave assisted extraction (MAE) by using ethanol as solvent.Beside that,this research also to investigate the influence of extraction time on castor oil yield.As for the last objective is to characterize the main composition from the castor oil by using the GC-MS.The solvent used in this method is ethanol due to relatively good absorber for microwave energy.In this research, the methods used were drying, grinding, extraction, separation and analysis.From the research, the highest oil yield is at 60 minute with 58% ,followed by by 50 minute with 55%,40 minute with 53 %, 30 minute with 50 %,20 minute with 47 % and lastly 10 minute with 45%.The major components of castor oil detected by GC-MS are ricinoleic acid,linoleic acid and oleic acid.